Design and Application of Reliability Calculation Program Based on Secondary Development of ABAQUS - ZOU Hong; WU Jian; XU Zhichun; YANG Li (Renmin Zhujiang)
As a kind of finite element analysis software,ABAQUS is widely used in nonlinear simulation field,but there is no universal and mature reliability calculation module.Therefore,it is necessary to establish a general reliability calculation program for Monte Carlo simulation based on finite element model to meet the automation requirements of reliability calculation of various structures in ABAQUS.This paper firstly puts forward the design idea and main functions of reliability calculation program in ABAQUS,including random number generation,model batch building,automatic result extraction and so on;then,develops the pre-processing and post-processing modules of ABAQUS with Python language for modularizing the main functions of the program;finally,introduces the application method of this reliability calculation program in detail taking the reliability calculation process of the finite element model of a simply supported steel truss bridge as an example.This reliability calculation program can effectively improve the degree of automation in the process of structural reliability calculation,and reduce the calculation time,which has great reference value in engineering application.